Impact of mode of anesthesia on ischemia modified albumin, operative conditions, and outcome in emergency craniotomies - Omyma Shehata Mohamed; Mohab Mohamad Darwish; Mahmoud Mohamed Mousa; Abd Elrahman Hassan Abd Elaziz; Ahmed Korani Mohamed (Egyptian Journal of Anaesthesia, 2023)
ABSTRACTBackground In neurosurgical procedures, selection of anesthetic techniques can have a substantial role in neurological outcome. Ischemia modified albumin (IMA) is a promising biomarker in strokes either hemorrhagic or ischemic. This work tried to explore the impact of type of the used anesthetics on operative condition, outcome, and if it can affect the level of IMA after emergency craniotomies.Methodology Fifty-four patients, 18–69 years of either sex, GCS>8, who underwent emergency craniotomies were enrolled into two groups where anesthesia was maintained by either: isoflurane ≤ 1Mac + fentanyl 1 mcg/kg/h. (Group I (inhalational)) or propofol infusion (100–150 mcg/kg/min) + dexmedetomedine 0.3mcg/kg/h. (Group P (TIVA)). Intraoperative hemodynamics, ICP, brain relaxation score, blood loose, and surgeon satisfaction were assessed. Also, recovery conditions, ICU stay, any complication and mortality, pre- and postoperative IMA and GCS were followed and analyzed.Results Group (P) revealed lower but steadier hemodynamics, significantly better brain relaxation score, lower ICP, adequate CPP, fewer patients needed blood transfusion, better surgeon satisfaction, and significantly shorter extubation time with higher sedation. Elevation in postoperative IMA was reported in both groups but the times of increase were significantly lower in group (P) with significant correlation between IMA level and GCS at all times that were detected in both groups. The two groups were comparable regarding postoperative complications, GCS, mortality, and ICU stay.Conclusion In emergency craniotomies, the use of TIVA (propofol + dexometomidine) produced lower ICP, better brain relaxation, and shorter extubation time with lower postoperative IMA level than inhalational anesthetics, which correlate well with GCS.